(untitled) (jornal of the libyan geographical society, 2011)
Environmental issues and problems have become so serious that individual countries are unable to confront and address them with their own resources. Furthermore, environmental issues have multifaceted social, economic, and security dimensions. Therefore, the report issued by the United Nations World Commission on Environment and Development, under the theme "Our Common Future," highlighted this. Environmental degradation has indeed become a source of political unrest and international tension in parts of Latin America, Asia and Africa.